Region reaching control of robot manipulators - Wang, Dequn (2008)
In this thesis, a new control con- cept called region reaching control for robot manipulators is proposed. In this new control concept, the desired objective can be specified as a region instead of a point. Several region reaching controllers are proposed in both joint-space and task-space. Since the desired region can be specified arbi- trarily small, the region reaching control concept is also a generalization of setpoint control problem.